Steel Structures Research Update: Innovative Steel Deck System for Highway Bridge Applications - Liu, Judy (Engineering Journal, 2024)
<span data-sheets-root="1" data-sheets-value=""1":2,"2":"Ongoing research on innovative steel bridge decks is highlighted. This study, currently under way at the University of Kansas, is led by Dr. William Collins, Associate Professor in the Department of Civil, Environmental, and Architectural Engineering. Dr. Collins’s research interests include fatigue and fracture of metallic structures; bridge design, fabrication, construction, and performance; and evaluation and preservation of historic structures. Among Dr. Collins’s accolades are the Robert J. Dexter Memorial Award, a Fulbright Scholar Award to conduct fracture mechanics research in Finland, and the AISC Milek Fellowship. The four-year Milek Fellowship is supporting this research on innovative steel deck systems for highway bridge applications—the first Milek Fellowship project to focus on bridges. Selected highlights from the work to date are presented, along with a preview of future research tasks."" data-sheets-userformat=""2":13249,"3":"1":0,"9":0,"10":0,"11":3,"12":0,"15":"Calibri","16":10">Ongoing research on innovative steel bridge decks is highlighted. This study, currently under way at the University of Kansas, is led by Dr. William Collins, Associate Professor in the Department of Civil, Environmental, and Architectural Engineering. Dr. Collins’s research interests include fatigue and fracture of metallic structures; bridge design, fabrication, construction, and performance; and evaluation and preservation of historic structures. Among Dr. Collins’s accolades are the Robert J. Dexter Memorial Award, a Fulbright Scholar Award to conduct fracture mechanics research in Finland, and the AISC Milek Fellowship. The four-year Milek Fellowship is supporting this research on innovative steel deck systems for highway bridge applications—the first Milek Fellowship project to focus on bridges. Selected highlights from the work to date are presented, along with a preview of future research tasks.